Tingkat Kepatuhan Pelaksanaan Protokol Kesehatan, Penggunaan Masker Dan Penanganannya Pada Pekerja Sektor Formal - Veronika, Erna; Irfandi, Ahmad; Azteria, Veza; Simatupang, Meithyra Melviana (Mahesa Research Center, 2024)
One of the highest clusters of COVID-19 cases in DKI Jakarta is the office cluster, attributed to the lack of compliance among employees with health protocols. The potential transmission to employees' families exacerbates the situation, even leading to temporary workplace closures. An initial survey revealed that 53.3% of employees do not adhere to COVID-19 health protocols in the workplace. This study aims to evaluate the compliance level with health protocols, mask usage, and mask waste management among formal sector workers in DKI Jakarta. The research follows a descriptive method with a cross-sectional design. Data were collected via Google Form from all office workers in DKI Jakarta (n=288) using purposive sampling. Results indicate that 43.8% of workers do not comply with health protocols, 66% do not properly manage used masks, increasing contamination risks, and only 28.5% use N95/KN95/KF94 masks. Companies are urged to enforce surveillance and impose sanctions for policy violations.